Convergent Evolution of Wingbeat-Powered Anti-Bat Ultrasound in the Microlepidoptera - O’Reilly, Liam Joseph; Harris, Brogan John; Agassiz, David John Lawrence; Holderied, Marc Wilhelm (Frontiers in Ecology and Evolution, 2021)
Bats and moths provide a textbook example of predator-prey evolutionary arms races, demonstrating adaptations, and counter adaptations on both sides. The evolutionary responses of moths to the biosonar-led hunting strategies of insectivorous bats include convergently evolved hearing structures tuned to detect bat echolocation frequencies. These allow many moths to detect hunting bats and manoeuvre to safety, or in the case of some taxa, respond by emitting sounds which startle bats, jam their biosonar, and/or warn them of distastefulness. Until now, research has focused on the larger macrolepidoptera, but the recent discovery of wingbeat-powered anti-bat sounds in a genus of deaf microlepidoptera (Yponomeuta), suggests that the speciose but understudied microlepidoptera possess further and more widespread anti-bat defences. Here we demonstrate that wingbeat-powered ultrasound production, likely providing an anti-bat function, appears to indeed be spread widely in the microlepidoptera; showing that acoustically active structures (aeroelastic tymbals, ATs) have evolved in at least three, and likely four different regions of the wing. Two of these tymbals are found in multiple microlepidopteran superfamilies, and remarkably, three were found in a single subfamily. We document and characterise sound production from four microlepidopteran taxa previously considered silent. Our findings demonstrate that the microlepidoptera contribute their own unwritten chapters to the textbook bat-moth coevolutionary arms race.